Literature Review of the Effects of Long-Term Opioid Use in the Management of Pain - Mahdi H. Alsugoor (Pakistan Journal of Medical & Health Sciences, 2022)
The interminable need to alleviate or sometimes eliminate pain has been perceived by all cultures around the globe for many centuries. The human species has found ways to perform pain management, including oral ingestion of herbs and utilization of procedures believed to have special remedial properties. The current medical practice calls for the application of opioids in the management of pain and this choice spans decades. From a general perspective, medical practitioners globally agree on the appropriateness of opioid use in the management of acute and chronic pain. Looking at the issue further, a huge controversy arises when the discussion spirals into whether the pros outweigh the cons in the long-term management of pain, especially chronic pain. Opiates belong to a class of drugs that are extracted from the latex sap of the opium poppy (Papaver somniferum) where they occur naturally as alkaloids. The term opioids, also commonly referred to as narcotics (a non-scientific term), is pharmacologically used to refer to artificial or natural chemical compounds that bind to opioid receptors and are antagonized by naloxone. The chemical composition, pharmacodynamics, and pharmacokinetics of opioids are beyond the scope of this review article, whose focus will be mainly aimed at discussing the apparent effects of long-term use of these drugs in pain management. Keywords: opioids, opiates, narcotics, pain, chronic pain, pain management, long-term use effects